Targeted capture sequencing identifies novel genetic variations in Chinese patients with idiopathic inflammatory myopathies. (26th August 2018) - Peng, Qing‐Lin; Lin, Jin‐Ming; Zhang, Yong‐Biao; Zhang, Xue‐Zhi; Wang, Pan‐Pan; Wu, Ting‐Ting; Yu, Jun; Dong, Xiao‐Qun; Gu, Ming‐Liang; Wang, Guo‐Chun
Abstract: Objectives: Previous association studies have identified genetic variants in the human leukocyte antigen (HLA) complex as substantial risk factors for idiopathic inflammatory myopathies (IIMs). However, a great number of genes are located in the HLA region, and thus fine mapping is quite necessary. Methods: Targeted capture sequencing were performed on the whole HLA region in 42 IIM patients and 24 healthy controls. A microarray analysis was applied to analyze gene expression profiles in additional 20 newly diagnosed IIM and five healthy controls. Results: The HLA region was confirmed to be associated with IIMs in Chinese patients. By gene expression profiling and pathway analysis, several genes were identified as candidates for IIM risk factors, including HLA‐A, HLA‐B, HLA‐DRB5, HLA‐DRB1, HLA‐DQA1, HLA‐DQB1 and HLA‐DQB2 . Interestingly, p.Y107V of the HLA‐DRB1 was predicted to be a potential causal non‐synonymous variation for IIMs that may affect the antigen‐binding groove of the HLA‐II molecule. Conclusions: Our data have revealed novel genetic variations in the HLA region of IIM patients and provide new insight into the pathogenesis and diagnosis of IIMs.